Answer: -4
Step-by-step explanation:
So, for y=3x-7, substitute the x with 1 (from (1,?) ) which gives you y=3(1)-7. Lastly, when you solve the equation, it would give you y=-4.
What would be equal would be 6.60, because 100/5 is 20. So 3 times 20 is 60. Plus the six so 6+0.6 is 6.60.
Answer:
2x + 3y = 13
4x - y = -2
In the second equation, subtract 4x from both sides.
-y = -2 - 4x
Divide both sides by -1.
y = 2 + 4x
Put this into the first equation in place of y.
2x + 3(2 + 4x) = 13
Multiply everything in the parenthesis by 3.
2x + 6 + 12x = 13
Combine like terms.
14x + 6 = 13
Subtract 6 from both sides.
14x = 7
Divide 14 on both sides.
x = 7 / 14
x = 0.5
Put this into the second equation in place of x.
4(0.5) - y = -2
2 - y = -2
Subtract 2 from both sides.
-y = -4
Divide both sides by -1.
y = 4
So x = 0.5 and y = 4.
Step-by-step explanation: